Gambaran Pengetahuan dan Kepatuhan Sivitas Akademika Universitas Al-Azhar Indonesia dalam Membaca Label Pangan - Widiawati, Dina; Giovani, Sarah; Puteri, Nafisah Eka; Shiba, Hauyus (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2022)
The busyness and lifestyle of modern society today tends to like instant things, including choosing food products. This is because packaged food products are more practical, easy to carry, widely available, and easy to consume. An analysis is needed regarding the level of knowledge and compliance of the community, especially the academic community of University Al-Azhar Indonesia (UAI) in this regard, so that the community can increase knowledge and compliance in reading packaged food labels when consuming or buying a product. The design of this study used a descriptive correlational design with a purposive sampling technique. Respondents in this study were a sample of UAI's still active academicians consisting of lecturers, educators, and students. The number of respondents in this study were 69.5% women and 30.5% men. In terms of age, most were 18-35 years old (93.90%). Respondents get the most source of food label information through online and print media. The priority of respondents when buying packaged food products is mostly choosing the name of the product (41.46%), then paying attention to the halal logo (37.80%). The priority level and respondents' knowledge when buying a packaged food product were mostly in the good category (75.61%). Respondent compliance level is also in good category (48.78%). The results of this study indicate that many respondents, namely UAI academicians, are accustomed to reading food labels when buying a packaged food product.Keywords – Community, Compliance, Food Label, Knowledge, Overview